Existing and Expected Service Quality of Grameenphone Users in Bangladesh - Ullah, Azmat; Rahman, Md. Hasebur (The Asian Journal of Technology Management (AJTM), 2015)
Abstract. The Grameenphone (GP) is a market leader in the telecommunication industry in Bangladesh. This study investigates the existing and expected service quality of Grameenphone users in Bangladesh. The Study reveals that there are significant gap between existing and expected perceived service network, 3G, customer care, physical facilities, billing cost, information service, mobile banking and GP offers. The study concludes that customer satisfaction is a dynamic phenomenon. Maintaining desired level of customer satisfaction requires corporate proactive responsiveness in accessing, building & retaining satisfied customers for sustainable competitive advantages in the marketplace.Keywords: Service Quality, Customer Satisfaction, Existing Service Quality, Expected Service Quality, GrameenphoneÂ